Biliary atresia: the role of gut microbiome, and microbial metabolites - Feng, Sansan; Cheng, Yongkang; Sheng, Chuqiao; Yang, Chunfeng; Li, Yumei (Frontiers in Cellular and Infection Microbiology, 2024)
Biliary atresia (BA) is a progressive fibroinflammatory disease affecting both the extrahepatic and intrahepatic bile ducts, potentially leading to chronic cholestasis and biliary cirrhosis. Despite its prevalence, the exact mechanisms behind BA development remain incompletely understood. Recent research suggests that the gut microbiota and its metabolites may play significant roles in BA development. This paper offers a comprehensive review of the changing characteristics of gut microbiota and their metabolites at different stages of BA in children. It discusses their influence on the host’s inflammatory response, immune system, and bile acid metabolism. The review also explores the potential of gut microbiota and metabolites as a therapeutic target for BA, with interventions like butyrate and gut microbiota preparations showing promise in alleviating BA symptoms. While progress has been made, further research is necessary to untangle the complex interactions between gut microbiota and BA, paving the way for more effective prevention and treatment strategies for this challenging condition.